Analisis Perlakuan Akuntansi Pembiayaan Qardhul Hasan Pada Bank Wakaf Mikro - Ahmad Nurcholis; Fadlil Abdani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Micro Waqf Bank is one of the Islamic Financial Institutions which is a government program that aims to prosper the economic life of the community by using the Qardhul Hasan contract in carrying out its financing transactions. Islamic Financial Institutions have guidelines, namely PSAK No. 59 and PSAK No. 101 in the preparation of its financial statements. The Financial Report itself is a manifestation of the responsibility of BWM managers to OJK and LAZNAS in carrying out and operating the BWM. This study uses a qualitative method. The results of the research obtained are that there are still many errors or discrepancies in the financial reporting of Qardhul Hasan financing which is adjusted to PSAK No. 59 and PSAK No. 101 both in the recognition, measurement, presentation and disclosure of the BWM financial statements